Pengaruh Kondisi Kelas Terhadap Keaktifan Belajar Anak di Sekolah Menengah Pertama Dwi Dharma Desa Kedungpari Kec.Mojowarno Jombang - Hakim, Dhikrul; Syafi’i, Muhammad; Aini, Alvin Nur Aini (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2024)
The purpose of this research was to describe classroom conditions as a strategy for success in creating a conducive class, to describe students’ learning activities before or after implementing class Classroom management strategies, to prove the effect of the classroom conditions on students’ learning activities in SMP Dwi Dharma Desa Kedungpari Kec. Mojowarno. This research used quantitative research methods. Data collection of his method were used observation, documentation and questionnaires. The results of the research are (1) the condition of the class contained a percentage calculation result of 70.45%. Namely categorized as good enough. Because it falls in the range of 56% -75%, which is in the quite good category. (2) the active learning of students havea percentage calculation result of 0.71%. That is categorized as not good. Because it falls in the range <40% -0%, which is in the bad category. (3) it is proven that the sig. (p.value) shows a number of 0,000, which means the value of sig (p.value) <0.05, thus Ha is accepted and H0 is rejected, meaning that there is an influence between class conditions on student's learning activeness.